Piper crotatum leaves extract reduced fasting blood glucose and glycated albumin but has lower efficacy than metformin in diabetic rats - Muhammad Rahmatullah; Wimpie Pangkahila; A.A. Gede Budhiarta (Fakultas Kedokteran Universitas Udayana, 2020)
Introduction: Piper crocatum leaves extract has been widely proven in reducing blood glucose levels in rats. However, there is still no study that compared its effectiveness to metformin. Therefore, this study aimed to evaluate the efficacy of Piper crotatum leaves extract compared to metformin in reducing fasting blood glucose and glycated albumin. Methods: Experimental pretest-posttest groups study using 16 adult male Wistar rats, aged 2-3 months, and weighing 200-220 grams was conducted. Diabetes was induced by using Streptozotocin and Nicotinamide intraperitonially. The control group was treated with metformin 9 mg/200gBB/day while the treatment group was treated by Piper crocatum leaves extract at 0.6 g/200gBB/day for 14 days. Venous blood sample was used to assess fasting blood glucose and glycated albumin. Resuts: The mean of fasting blood glucose level decreased significantly in the control group from 182.00+19.38 mg/dl to 117.38+12.51 mg/dl (p<0.001) and the levels of GA was also decreased from 3.04+0.99 ng/ml to 1.38+0.63 ng/ml (p<0.001). In the treatment group, the level of fasting blood glucose decreased from 179.50+24.39 mg/dl to 140.13+15.12 mg/dl (p<0.001) and the levels of glycated albumin was also decreased from 4.01+1.12 ng/ml to 3.58+0.90 ng/ml (p=0.036). There was no difference in the level of fasting blood glucose and GA between the two groups before treatment but both parameters were significantly lower compared to the treatment group (p=0.005 and p<0.001 respectively). Conclusion: Administration of piper crotatum leaves extract reduced fasting blood glucose but has lower efficacy compared to metformin in diabetic Wistar rats.